Oncolytic viruses in cancer therapy: Exploring the mechanisms and clinical potential of mammalian and avian reoviruses - Yi-Ying Wu; Ming-Shan Chen; Tsai-Ling Liao; Muhammad Munir; Hung-Jen Liu (Tungs’ Medical Journal, 2025)
Oncolytic viruses (OVs) can selectively infect and lyse cancer cells while simultaneously activating the host immune system and making them a prospective class of anticancer immunotherapeutic agents. In particular, mammalian reovirus (MRV) and avian reovirus (ARV) have gained unique attention for their significant properties and clinical potentials. This review explores their mechanisms of action, immunological interactions, and clinical applications in OV therapy. Studies have shown that MRV exploits defective antiviral responses in cancer cells to induce apoptosis and autophagy, whereas ARV modulates mTORC1 and energy metabolism pathways to enhance viral replication. Both OVs elicit robust innate and adaptive immune responses, which are critical for long-term antitumor immunity. Combining OVs with chemotherapy and immunotherapy has shown synergistic effects, enhanced antitumor responses, and overcome treatment resistance. However, challenges around managing the host immune response and the efficient delivery of the virus remain unresolved. Ongoing and future clinical trials are pivotal in validating the therapeutic potential of these OVs and considering them as innovative approaches in the oncology landscape.